Comparison of posterior capsule opacification after two different surgical methods of cataract extraction - Nekolová, Jana; Pozlerová, Jana; Jirásková, Naďa; Rozsíval, Pavel; Kadlecová, Jana (American journal of ophthalmology, 2008)
PURPOSE: To compare the extent of posterior capsule opacification (PCO) after AquaLase and NeoSoniX phacoemulsification methods using two types of software for PCO quantification. DESIGN: Prospective, randomized clinical trial. METHODS: At the Department of Ophthalmology, University Hospital in Hradec Kralove, 50 patients (100 eyes) were analyzed one year after surgery. AquaLase was used in the right eye and NeoSoniX in the left eye of each patient. One year after surgery, digital retroillumination photographs of anterior segments were obtained. The Evaluation of Posterior Capsule Opacification (EPCO) 2000 software (Berlin, Germany) and the Open-Access Systematic Capsule Assessment (OSCA) system (Edinburgh, United Kingdom) were used for PCO assessment. Best-corrected Snellen visual acuity (BCVA) was evaluated before and after surgery. Statistical analysis was performed using parametric tests. RESULTS: The EPCO 2000 results were as follows: mean value for right eyes, 0.324+/-0.305; mean value for left eyes, 0.298+/-0.341; no difference was proved (P=.532). The OSCA results were as follows: for right eyes, 0.7097+/-0.3777; for left eyes, 0.8584+/-0.4323; significant difference (P=.046), worse for left eyes. No correlation between EPCO 2000 and OSCA results was established (P>.001; correlation coefficient, 0.347). BCVA for the right eyes was 0.837+/-0.262 and for the left eyes was 0.849+/-0.224. Neodymium:yytrium-aluminum-garnet capsulotomy was performed in one eye in the NeoSoniX group, and in no eyes in the AquaLase group. CONCLUSIONS: There was no significant difference in PCO measured by EPCO 2000, however, PCO after AquaLase as assessed by EPCO 2000 was slightly denser. The OSCA system gave significantly higher scores in the NeoSoniX group. No correlation between EPCO 2000 and OSCA outcomes was proved.
Keywords: katarakta; Anterior Eye Segment; financování organizované; mužské pohlaví; Male; Financing, Organized; senioři; senioři nad 80 let; Visual Acuity; Female; Humans; Software; software; pooperační komplikace; lidé; Prospective Studies; přední segment oční; Middle Aged; ženské pohlaví; implantace nitrooční čočky; lidé středního věku; Lens Capsule, Crystalline; Postoperative Complications; Aged, 80 and over; Randomized Controlled Trials as Topic; randomizované kontrolované studie jako téma; Lens Implantation, Intraocular; prospektivní studie; fakoemulzifikace; dospělí; Adult; Cataract; zraková ostrost; Phacoemulsification; Aged; pouzdro oční čočky